Association of latent tuberculosis infection in health care workers with allergy and allergic sensitization to common aeroallergens - Banić, Ivana (Array, 2020)
Health care workers (HCW) are at increased risk of a latent tuberculosis infection (LTBI) due to occupational exposure to Mycobacterium tuberculosis. In order to investigate the mutual influence of a TH1 type immune response caused by LTBI and T helper 2 (TH2) type immune response caused by allergy, we conducted a study examining the prevalence of common inhaled allergen sensitization in the HCW population with different levels of exposure to tuberculosis (high and low). HCW with possible exposure to tuberculosis (TB) were tested with QuantiFERON-TB Gold (QFT-G) and tuberculin skin test (TST), while skin prick test (SPT) was performed for inhaled allergens. The antigen (Ag) response at QFT-G was inversely correlated with participants` allergy anamnesis (p= 0.039). Sensitization to inhaled allergens (positive SPT and number of positive allergens at SPT) was more prominent in the low exposure group (p= 0.006 and p= 0.0065, respectively). Ag response at QFT-G test was significantly higher in participants with no medical history of allergy (p= 0.048). Our results demonstrate that exposure to TB and LTBI are associated with inhaled allergen sensitization in HCW, possibly inhibiting allergic sensitization by mediating the T-helper type 1 (Th1) immune response.